An Experimental Investigation of F-K Migration and SAR Algorithm using Beam Space MUSIC for UWB Through-the-Wall Imaging - Bektas, Huseyin Onder; Ozdemir, Ozgur; Orhan, Melek; Turk, Ahmet Serdar (IEEE, 2016)
In this paper, we have applied and discussed the frequency - wavenumber migration, synthetic aperture radar algorithm and conventional delay and sum beamforming for through the wall imaging radar signals with high performance of target detection. After we obtained the beam domain data, we also applied MUSIC algorithm that is one of the subspace methods. In test measurements, we used ultra-wide band a step frequency continuous wave based radar and impulse ground penetrating radar system to collect A-scan data. In order to distinguish the concealed targets, A-scan data was demonstrated in B-scan image.
Keywords: through the wall radar imaging; synthetic aperture radar algorithm; frequency wavenumber migration; multiple signal classification; impulse radar; stepped frequency radar; RADAR; Engineering; Physics